Compute this equation of logarithms under a squareroot

Algebra Level 3

log 2 ( 3 ) log 2 ( 12 ) log 2 ( 48 ) log 2 ( 192 ) + 16 log 2 ( 12 ) log 2 ( 48 ) + 10 = ? \sqrt{\log_2(3)\log_2(12)\log_2(48)\log_2(192)+16} - \log_2(12)\log_2(48) + 10 = \ ?


The answer is 6.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

I'll just focus to the harsh square root over there. Note that inside of the logarithms can be factored. Manipulating stuff and we get log 2 ( 3 ) log 2 ( 12 ) log 2 ( 48 ) log 2 ( 192 ) + 16 = log 2 ( 3 ) log 2 ( 3 2 2 ) log 2 ( 3 2 4 ) log 2 ( 3 2 6 ) + 16 = log 2 ( 3 ) [ log 2 ( 3 ) + 2 ] [ log 2 ( 3 ) + 4 ] [ log 2 ( 3 ) + 6 ] + 16 \begin{aligned} \sqrt{\log_{2}(3)\log_{2}(12)\log_{2}(48)\log_{2}(192)+16} &= \sqrt{\log_{2}(3)\log_{2}(3\cdot 2^2)\log_{2}(3\cdot 2^4)\log_{2}(3\cdot 2^6)+16} \\ &= \sqrt{\log_{2}(3)[\log_{2}(3) + 2][\log_{2}(3) + 4][\log_{2}(3) + 6]+16} \end{aligned} Let y = log 2 ( 3 ) + 3 y = \log_{2}(3) + 3 . Then the expression becomes ( y 3 ) ( y 1 ) ( y + 1 ) ( y + 3 ) + 16 = ( y 2 1 ) ( y 2 9 ) + 16 = ( y 4 10 y 2 + 9 ) + 16 = y 4 10 y 2 + 25 = ( y 2 5 ) 2 = y 2 5 \begin{aligned} \sqrt{(y - 3)(y - 1)(y + 1)(y + 3)+16} &= \sqrt{(y^2 - 1)(y^2 - 9)+16} \\ &= \sqrt{(y^4 - 10 y^2 + 9)+16} \\ &= \sqrt{y^4 - 10 y^2 + 25} = \sqrt{(y^2 - 5)^2} = y^2 - 5 \end{aligned} The value requested now is just log 2 ( 3 ) log 2 ( 12 ) log 2 ( 48 ) log 2 ( 192 ) + 16 log 2 ( 12 ) log 2 ( 48 ) + 10 = ( log 2 ( 3 ) + 3 ) 2 5 ( log 2 ( 3 ) + 2 ) ( log 2 ( 3 ) + 4 ) + 10 = ( log 2 2 ( 3 ) + 9 + 6 log 2 ( 3 ) ) 5 ( log 2 2 ( 3 ) + 6 log 2 ( 3 ) + 8 ) + 10 = 6 \begin{aligned} &\sqrt{\log_{2}(3)\log_{2}(12)\log_{2}(48)\log_{2}(192)+16} - \log_{2}(12)\log_{2}(48) + 10 \\ =&(\log_{2}(3) + 3)^2 - 5 - (\log_{2}(3) + 2)(\log_{2}(3) + 4) + 10 \\ =&(\log_{2}^{2}(3) + 9 + 6\log_{2}(3)) - 5 - (\log_{2}^{2}(3) + 6\log_{2}(3) + 8) + 10 = \boxed{6} \end{aligned}

Chew-Seong Cheong
Nov 21, 2018

x = log 2 ( 3 ) log 2 ( 12 ) log 2 ( 48 ) log 2 ( 192 ) + 16 log 2 ( 12 ) log 2 ( 48 ) + 10 = log 2 ( 3 ) log 2 ( 4 × 3 ) log 2 ( 16 × 3 ) log 2 ( 64 × 3 ) + 16 log 2 ( 4 × 3 ) log 2 ( 16 × 3 ) + 10 = log 2 3 ( 2 + log 2 3 ) ( 4 + log 2 3 ) ( 6 + log 2 3 ) + 16 ( 2 + log 2 3 ) ( 4 + log 2 3 ) + 10 Let log 2 3 = a = a ( 2 + a ) ( 4 + a ) ( 6 + a ) + 16 ( 2 + a ) ( 4 + a ) + 10 = a 4 + 12 a 3 + 44 a 2 + 48 a + 16 ( a 2 + 6 a + 8 ) + 10 = ( a 2 + 6 a + 8 ) 2 8 ( a 2 + 6 a + 8 ) + 16 ( a 2 + 6 a + 8 ) + 10 = ( a 2 + 6 a + 8 ) 4 ( a 2 + 6 a + 8 ) + 10 = 6 \begin{aligned} x & = \sqrt{\log_2(3)\log_2(12)\log_2(48)\log_2(192)+16} - \log_2(12)\log_2(48) + 10 \\ & = \sqrt{\log_2(3)\log_2(4\times 3)\log_2(16\times 3)\log_2(64\times 3)+16} - \log_2(4\times 3)\log_2(16\times 3) + 10 \\ & = \sqrt{\log_2 3(2+\log_23)(4+\log_2 3)(6+\log_2 3)+16} - (2+\log_23)(4+\log_2 3) + 10 & \small \color{#3D99F6} \text{Let }\log_2 3 = a \\ & = \sqrt{a(2+a)(4+a)(6+a)+16} - (2+a)(4+a) + 10 \\ & = \sqrt{a^4+12a^3+44a^2 +48a+16} - (a^2+6a+8) + 10 \\ & = \sqrt{(a^2+6a+8)^2-8(a^2+6a+8)+16} - (a^2+6a+8) + 10 \\ & = (a^2+6a+8) - 4 - (a^2+6a+8) + 10 \\ & = \boxed 6 \end{aligned}

Srinivasa Gopal
Nov 21, 2018

Log in the solution below refers to Log to the base 2.

Log(12) = Log(3*4) = Log(3) + Log(4) = Log(3) + 2;

Similarly Log(48) = Log(3) + Log(16) = Log(3) + 4; Log(192) = Log(3) + 6.

So the expression under the root is Log(3)(Log(3) +2)(Log(3)+4)(Log(3)+6) + 16.

Let us take Log(3) as equal to some var Y , the expression under the root can be written as as Y*(Y+2)(Y+4)(Y+6) + 16;

Reorder the product as Y(Y+6)*(Y+4)(Y+2) + 16 or (Y^2 + 6Y)(Y^2+6Y+8) + 16 , substitute Y^2 + 6Y as t ,so the expression becomes t^2 + 8t + 16 or just (t+4)^2.

So the expression under the root reduces to t+4 where t is...;

Now let us look at the expression outside the root -(log3 + log4)(log3 +log16) + 10 = -(log(3) + 2)(log(3) + 4) = -(X+2)(X+4) + 10 = - ( X^2 + 6X + 8) + 10 or -(t +8) +10 or 2 - t.

The sum of the entire expression reduces to t+4 + 2 - t = 6. So X = 6.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...